ICT in public examing in Nigeria: challenges and prospects (2013)
It is univesally acclaimed that examinations are vtial in offers to its citizens. This is why the use of Informations Computer Technology (ICT) that has been embrased by most of our public formal traditional system of service deliverance. This paper therefore made a review of ICT practices in public examining in order to see the extent to which they have met the global standards. It therefore highlighted the benefits of ICT usage, the challenges and prospects. Recommendations are also offered for improvement in public examining in general.